Assessment of in Situ Reductive Dechlorination Using Compound-Specific Stable Isotopes, Functional Gene PCR, and Geochemical Data (2009)
Isotopic analysis and molecular-based bioassay methods were used in conjunction with geochemical data to assess intrinsic reductive dechlorination processes for a chlorinated solvent-contaminated site in Tucson, Arizona. Groundwater samples were obtained from monitoring wells within a contaminant plume comprising tetrachloroethene and its metabolites, trichloroethene, cis-1,2-dichloroethene, vinyl chloride, and ethene, as well as compounds associated with free phase diesel present at the site. Compound-specific isotope analysis was performed to characterize biotransformation processes influencing the transport and fate of the chlorinated contaminants. Polymerase chain reaction (PCR) analysis was used to assess the presence of indigenous reductive dechlorinators. The target regions employed were the 16s rRNA gene sequences of Dehalococcoides sp. and Desulfuromonas sp. and DNA sequences of genes pceA, tceA, bvcA, and vcrA, which encode reductive dehalogenases. The results of the analyses indicate that relevant microbial populations are present and that reductive dechlorination is presently occurring at the site. The results further show that potential degrader populations as well as biotransformation activity is nonuniformly distributed within the site. The results of laboratory microcosm studies conducted using groundwater collected from the field site confirmed the reductive dechlorination of tetrachloroethene to dichloroethene. This study illustrates the use of an integrated, multiple-method approach for assessing natural attenuation at a complex chlorinated solvent-contaminated site.